Pentecostalism and Neo-Liberal Capitalism: Faith, Prosperity and Vision in African Pentecostal-Charismatic Churches - Meyer, Birgit (Journal for the Study of Religion, 2007)
Focusing on the phenomenal popularity of Pentecostal-Charismatic Churches (PCCs) in Africa, this article addresses the apparent consonance between the rise of this type of Christianity and the spread of neo-liberal capitalism. It is argued that Max Weber's Protestant Ethic can serve as a source of inspiration for grasping this phenomenon, but should not be employed as a blue print because this would blind us to certain aspects of PCCs that markedly digress from Weber's model. A plea is made for investigating central features of PCCs—the emphasis on Born Again faith in miracles, the promise of Prosperity, and the entanglement of media with the message—so as to gain insight in their enmeshment with capitalism, as well as into the internal limitations and contradictions implied by this.
free